A Narrative Inquiry Into Indigenizing School Mathematics Through Miyō-pimōhtēwin and Kamskénow - Stavrou, Stavros Georgios (Frontiers in Education, 2021)
In Canadian mathematics education, dominant colonial narratives highlight an achievement disparity between Indigenous and non-Indigenous students in a way that often re-inscribes perceived deficits of Indigenous students, ignores the educational aspirations of Indigenous peoples, and sidelines Indigenous cultural and linguistic representations of knowledge in the classroom. Intentions of Indigenizing curriculum include challenging and reversing racist and colonial ideologies that hinder Indigenous education, providing meaningful alternatives within school cultures that foreground essential aspects of Indigenous education, and supporting the dynamic learning of Indigenous students. In my research described in this article, I used a narrative inquiry to describe how two Cree elementary school teachers shared promising practices of holistic assessments in school mathematics that centred their Cree language, miyō-pimōhtēwin, and kamskénow.